Waiting reasons affecting the handling process at liquid bulk terminals - Eren Salihoglu; Elif Bal Beşikçi (Journal of Shipping and Trade (JST), 2022)
Since liquid bulk cargoes are the most frequently handled cargo types in Turkish ports in 2019 and the latter in 2020, the loading and unloading times of liquid bulk cargoes are important in terms of handling efficiency. While a higher amount of cargo handled per unit time increases the profitability for terminal operations, the short handling time of tankers at the terminal provides an advantage for the next voyage. In this study, the process in the terminals in Turkey where 19.05% of the total liquid bulk cargo handled was reviewed as well as the reasons for the waits in this process. Thus, it was aimed to find subjects that need to be focused on to reduce the waiting times. An expert team was asked to indicate the reasons for the waits using the fishbone method. In addition, a questionnaire was applied to a sample group of 134 people who were the stakeholders of the handling process. It was found out that the reasons for the waits obtained through the questionnaire matched those determined by the fishbone method. To reach a solution, prioritization was provided by scoring the reasons that lead to waits.
Keywords: 650; Efficiency; Handling; Liquid bulk cargo; Port; Reasons for the waits; Terminal